An observational maximum seasonal freeze depth changes for a province. (24th June 2019) - Li, Liguang; Yang, Hongbin; Ding, Kangkang; Wang, Hongbo; Zhao, Ziqi
Frozen ground plays an essential role in high latitude regions of northern hemisphere, and it is an important indicator of climate change. We analysed temporal and spatial variations of the maximum seasonal freeze depth (MSFD) from 1965 to 2015 in 53 stations of Liaoning province in China. The results indicate that the average MSFDs in each month are different, with the highest value of 93 cm in February. The annual MSFD is in a decreasing trend with the rate of −5.25 cm per decade. The spatial distribution of MSFD is in a pattern of decreasing from the northwest to the southeast. The response of the MSFD to global warming showed that the relationships of MSFD with the air temperature and the North Atlantic Oscillation (NAO) are negative. The starting and ending dates of the MSFD are in delaying and moving ahead trends. The 100 cm MSFD line moved northward gradually.